Pengaruh Modal, Sikap Kewirausahaan, dan Pengalaman Usaha terhadap Pendapatan UMKM di Kecamatan Parungponteng Tasikmalaya - Risa Amelia; Raskadi R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in boosting the local economy. However, most MSME operators in Parungponteng Subdistrict, Tasikmalaya, continue to experience stagnant or even declining income, despite the growing number of MSMEs. This situation is believed to be influenced by capital, entrepreneurial attitudes, and business experience; therefore, research is needed to determine the impact of these three factors on MSME income. The objective of this study is to determine the influence of capital, entrepreneurial attitudes, and business experience on MSME income in Parungponteng Subdistrict, Tasikmalaya. The research method used is a quantitative method with descriptive and verifiable approaches. The population in this study consists of 2,710 MSMEs, with a sample of 96 respondents selected using purposive sampling. Data collection was conducted through the distribution of questionnaires. Data analysis involved validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination, all performed using SPSS version 27. The results of the study show that capital and entrepreneurial attitudes have a partial effect on MSME revenue, while business experience has no partial effect on revenue. Collectively, capital, entrepreneurial attitudes, and business experience influence MSME revenue in the Parungponteng subdistrict of Tasikmalaya.A B S T R A K